Green space access in the neighbourhood and childhood obesity - Jia, Peng; Cao, Xinxi; Yang, Hongxi; Dai, Shaoqing; He, Pan; Huang, Ganlin; Wu, Tong; Wang, Yaogang (Obesity reviews, 2021)
Summary Access to green space may influence individual physical activity (PA) and subsequently weight status, as increased exposure to green space could improve health by increasing opportunities and the actual levels of PA. However, whether such associations hold empirically remains inconclusive. This study reviewed articles that analysed the association between access to green space and weight‐related behaviours/outcomes among children, published before 1 January 2019. The sample sizes ranged from 108 to 44 278. Four cohorts and 17 cross‐sectional studies conducted in nine countries were identified. Overall, evidence showed a positive association between access to green space and PA and a negative association between access to green space and television‐watching time, body mass index (BMI) and weight status among children. Distance to the nearest green space, measured by geographic information system (GIS) in 10 studies, was often used to represent access to the nearest green space. It still remains difficult to draw a clear conclusion on the association between access to green space and BMI. Longitudinal studies can directly estimate the strength of the association between exposure and disease, which is needed to determine the causal association between access to green space and weight status.